Typy zachowań firm lokalnych wobec inwestorów zagranicznych - Gorynia, Marian (Kinds of Behaviour of Local Firms Towards Foreign Investors, 2005)
The increasing openness of Polish economy for various forms of economic cooperation with foreign countries, raises a question, about the way local companies behave, can behave and should behave - faced with growing expansion and competitive pressure of the foreign companies. Literature concerning this subject is not very wide, the authors of the publications focus their attention on the behavior of the companies pursuing expansion, whereas the companies affected by it are most of the lime treated as minor, and are being given less attention. The aim of this paper is a synthetic presentation and evaluation of usefulness of hitherto existing literature/output. From among the scientific descriptions of this issue we shall point out three: the matrix of the local companies strategy by Dawar and Frost, the typology of local companies behavior by Gorynia and Wolniak, the conception of logistic strategies for global business by Cooper. The mentioned typologies may be used for three aims. First of all, this typologies make it possible to classify the real behaviors of local companies of the host country, by defining which type of behavior seems to suit best for a particular company. Second of all, the types mentioned can be used as models, patterns, kind of norms and standards, which may be the reference point for desirable or recommended behavior. Third of all the presented typologies may be useful for formulating recommendation for the economic politics.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1066, s. 110-123